Nucleolar Apparatus of Lymphocytes as an Indicator of Lymphoid Organs’ Functional Activity in the Context of Pre-Clinical Vaccine Evaluation - S. A. Bugorkova; T. N. Shchukovskaya; A. F. Kurylina (Проблемы особо опасных инфекций, 2015)
Studied has been the state of the nucleolar apparatus in lymphocytes of periphery lymphoid organs in laboratory animals vaccinated against plague and tularemia in order to evaluate predictive capability of the parameter in the context of pre-clinical evaluation of the vaccines under development, against particularly dangerous infections. For the detection of silver adjoining proteins, contained in the nucleolar organizer region (AgNOR), W.M.Howell and D.A.Black staining of semi-thin paraffin sections of lymphoid organs of the immunized BALB/c mice has been performed. For this purpose, ready-assembled panel, manufactured at BioVirtum, has been deployed. Under assessment of the functional state of immunogenesis organs in vaccinated against plague and tularemia animals revealed has been the increase in numbers of cells with three and more AgNOR-positive nucleoli in the nucleus of the lymphocytes of periphery organs of the biomodels’ immune system. It indirectly manifests proliferative capacity of immune system cellular component. Informativity of the quantitative evaluation of the cell proliferative activity by the reference to the status changes of AgNOR in the nuclei of immunogenesis organs’ lymphocytes makes it possible to entertain the possibility of introducing this method into the existing morphological vaccine quality assessment scheme at the stage of the pre-clinical trials.